Riuscirà l’essere umano a fermare la devastazione del proprio habitat? Una ricerca sugli studenti del terzo anno di Sociologia - Claudio Tognonato (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The article presents the results of an action-research study of the environmental crisis, which was carried out by two groups of third year students, from two different academic years, enrolled in the sociology degree program. The investigation, adhering to course regulations, was part of a departmental internship. The results offer us time to reflect and project upon the possibilities of stopping the ongoing destruction of environmental conditions, which are indispensable for life on earth. The whole of humanity is involved in a planetary problem that puts the very survival of our species at stake. We wonder if we are the point of no return and whether we are facing, and even capable of stopping, a process that now seems inescapable.